The balance of trade and the virtual water transfers: analysis of agricultural sector in CearÃ - SÃrgio Rodrigues Rocha (2014)
The concepts of virtual water and water footprint are being increasingly used as management tools and relevant indicators to the appropriation of water resources consumption. Virtual water is the amount of fresh water incorporated into the production process of any goods or services consumed by people. The objective of this research is to measure the balance of trade of virtual water, from 1997 to 2012, in the state of CearÃ. For this purpose, were selected the main agricultural commodities of export tariffs and import of commodities; well as was used to water footprint methodology,which includes direct and indirect consumption of water, at all locations in which occur the productive chains of goods and services. As a result of quantification, for the case study of CearÃ, which is located in the semiarid Northeast Brazil and faces problems of water shortages, imports exceed exports in 44,629,598.5 million liters of virtual water. CearÃ is, therefore, a net importer of virtual water. The United States is the main destination of CearÃ exports of virtual water (12,188,074.6 million liters). The Argentina is the principal source of imports of CearÃ of virtual water (42,219,370.0 million liters). Considering the total volume traded of virtual water, in liters, the main export products (cashews) and import (wheat) present, in liters per kilogram, patterns of total water footprints, respectively, 39,549.9 and 4,411.2. With the purpose of reducing the water footprint, of CearÃ products, may be employed in the agricultural sector for measures:increasing productivity green footprint (rainwater) in rainfed agriculture; add the total production in rainfed agriculture; increase productivity of blue footprint (surface or underground water) on irrigated agriculture; decrease the relationship between blue and green water footprints; reduce the footprint gray (polluted water), through the reduction of the use of artificial fertilizers and pesticides. So that consumers are made aware, with respect to the products they consume, it may be useful to put information about the water footprint on the labels of the goods.